A PRECAUTIONARY PRINCIPLE FOR DUAL USE RESEARCH IN THE LIFE SCIENCES - Kuhlau, Frida (Bioethics, 2011)
Most life science research entails dual-use complexity and may be misused for harmful purposes, e.g. biological weapons. The Precautionary Principle applies to special problems characterized by complexity in the relationship between human activities and their consequences. This article examines whether the principle, so far mainly used in environmental and public health issues, is applicable and suitable to the field of dual-use life science research. Four central elements of the principle are examined: threat, uncertainty, prescription and action. Although charges against the principle exist – for example that it stifles scientific development, lacks practical applicability and is poorly defined and vague – the analysis concludes that a Precautionary Principle is applicable to the field. Certain factors such as credibility of the threat, availability of information, clear prescriptive demands on responsibility and directives on how to act, determine the suitability and success of a Precautionary Principle. Moreover, policy-makers and researchers share a responsibility for providing and seeking information about potential sources of harm. A central conclusion is that the principle is meaningful and useful if applied as a context-dependent moral principle and allowed flexibility in its practical use. The principle may then inspire awareness-raising and the establishment of practical routines which appropriately reflect the fact that life science research may be misused for harmful purposes.